2016
DOI: 10.1038/modpathol.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Tumor eosinophil infiltration and improved survival of colorectal cancer patients: Iowa Women's Health Study

Abstract: The role of the innate immune response in colorectal cancer is understudied. We examined the survival of colorectal cancer patients in relation to eosinophils, innate immune cells, infiltrating the tumor. Tissue microarrays were constructed from paraffin-embedded tumor tissues collected between 1986–2002 from 441 post-menopausal women diagnosed with colorectal cancer in the Iowa Women’s Health Study. Tissue microarrays were stained with an eosinophil peroxidase antibody. Eosinophils in epithelial and stromal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 43 publications
7
93
1
Order By: Relevance
“…86-91), but by enhancing the infiltration of CD8 + T cells via secretion of chemoattractants and normalizing tumor vessels, thus providing a mechanistic link to understanding why an increased eosinophil count may herald a better outcome (92). Of note is that tumor eosinophil infiltration has been described as favorable (e.g., in colon cancer) (93) or unfavorable (94). Its occurrence and relevance in human melanoma remain to be studied in more detail, but it is striking that Soiffer et al observed both blood eosinophilia and degranulating eosinophils in regressing melanoma metastases upon vaccination with GM-CSF-secreting autologous melanoma cells (95).…”
Section: Discussionmentioning
confidence: 99%
“…86-91), but by enhancing the infiltration of CD8 + T cells via secretion of chemoattractants and normalizing tumor vessels, thus providing a mechanistic link to understanding why an increased eosinophil count may herald a better outcome (92). Of note is that tumor eosinophil infiltration has been described as favorable (e.g., in colon cancer) (93) or unfavorable (94). Its occurrence and relevance in human melanoma remain to be studied in more detail, but it is striking that Soiffer et al observed both blood eosinophilia and degranulating eosinophils in regressing melanoma metastases upon vaccination with GM-CSF-secreting autologous melanoma cells (95).…”
Section: Discussionmentioning
confidence: 99%
“…After scanning the titles and abstracts of the retrieved studies, we selected the full text of 15 original research articles in accordance with the objectives established and all articles were included in our review. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Data from the included studies were independently extracted from each study and comprised: author; year of publication; sample size; participants' characteristics (mean age and gender proportion); follow-up assessment; tumour classification, stage and clinicopathological features; TATE characterization (i.e. staining, count and location); and major findings.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Twelve studies associated TATE with survival and/or metastatic behaviour of CRC 9,11,12,[14][15][16][18][19][20][21][22][23] and three studies associated TATE with malignant progression of colorectal lesions. 10,13,17 The first set of studies evaluated 2523 CRCs.…”
Section: Baseline Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study published in the journal Modern Pathology in 2016. Prizement et al [3] looked at how eosinophils might predict outcomes for patients with colorectal cancer. Taghizadeh et al [4] found no associations between objective allergy markers and cancer in a total population but reported positivity and a high number of eosinophils with association to reduced risk to die of cancer in specific subgroups.…”
mentioning
confidence: 99%